Repeated biocide treatments cause changes to the microbiome of a food industry floor drain biofilm model - Kragh, Martin Laage; Scheel, Nanna Hulbæk; Leekitcharoenphon, Pimlapas; Truelstrup Hansen, Lisbeth (Frontiers in Microbiology, 2025)
There is a concern about the development of microbial tolerance and resistance to biocides due to their repeated use within the food industry. This study aimed to develop a floor drain biofilm model and test whether repeated biocide treatment would result in increased tolerance to biocides. Culturomics and shotgun metagenomic analysis of 14 drains and 214 bacterial isolates from three industrial food production environments revealed microbiomes with great diversity and complexity, but with the dominance of a few highly abundant taxa, including Pseudomonas. A representative drain biofilm was created (3 days, 15°C) using 31 whole genome sequenced bacterial isolates from 24 genera. The biofilm model represented 47–58% and 76–81% of the microbial abundance observed in the metagenome and viable microbiota, respectively. The biofilm model was exposed on days 3 and 6 to water or different industrial concentrations of benzalkonium chloride (BC), peracetic acid (PAA), or sodium hypochlorite (SH). Analysis of the viable survivors using MALDI-TOF MS and the regrowing biofilms using 16S rRNA amplicon sequencing showed how the diversity of the biofilm decreased but without any change in biocide tolerance as seen in log reductions (CFU/cm2). The use of different biocides did, however, exert significantly different selective pressures on the microbiomes as Citrobacter, Acinetobacter, Aeromonas, and Pseudomonas dominated the biofilm after treatments with SH or PAA, while Serratia and Moraxella dominated after treatments with BC. The dominance of Serratia marcescens could be explained by the carriage of a BC efflux pump (oqxB) and the highest (20 mg/L BC) minimum inhibitory concentration (MIC) result of the drain isolates. In contrast, despite carrying a BC efflux pump (qacH), Listeria monocytogenes ST121 did not show increased survival or presence in the biofilm after BC treatments. Only the highest tested concentration of PAA was able to completely eradicate L. monocytogenes. The developed biofilm model and the repeated biocide treatments enabled a better understanding of how biocides affect the biofilm microbiome. Future research should involve testing biocide rotation strategies to control biofilm regrowth and inactivation of persistent foodborne pathogens in floor drains.